Evaluation of Sexual Dysfunction in Females With Ankylosing Spondylitis - Halil Ekrem AKKURT,; Halim YILMAZ,; Sema YILMAZ,; Lütfiye PARLAK,; Banu ORDAHAN,; Ali SALLI, (Archives of Rheumatology, 2016)
Objectives: This study aims to evaluate sexual function in females with ankylosing spondylitis (AS), compare them with healthy controls, and demonstrate the effects of AS on female sexual functions. Patients and methods: Fifty-four AS patients (mean age 39.33±8.57 years; range 20 to 55 years) and 56 similar aged healthy controls were included in the study. Depression levels and sexual functions of all participants were evaluated by the Beck Depression Inventory and Female Sexual Function Index (FSFI), respectively. Other assessment methods included the visual analog scale for pain, fatigue, and importance of sexual life; Bath Ankylosing Spondylitis Disease Activity Index for disease activity, Bath Ankylosing Spondylitis Functional Index for functionality, Bath Ankylosing Spondylitis Metrology Index for spinal mobility, and Short Form-36 (SF-36) for quality of life. Results: Total FSFI and all FSFI subscale scores and number of weekly sexual intercourse were significantly lower while Beck Depression Inventory score was significantly higher in females with AS when compared to controls. In AS patients with depression, total FSFI score and FSFI subscales scores of desire and arousal were significantly lower than those without depression. In females with AS, there were negative correlations between total FSFI score and duration of complaint, Beck Depression Inventory score, Bath Ankylosing Spondylitis Metrology Index score, visual analog scale score, age, and duration of marriage while positive correlations existed between total FSFI score and visual analog scale importance of sexual life score and number of weekly sexual intercourse, SF-36 fatigue, SF-36 social function, SF-36 pain, and SF-36 mental component scores. Conclusion: Sexual dysfunction was more common in female AS patients without marked impairment in body image and hip involvement when compared to normal population. Sexual problems which are generally neglected should be handled regardless of disease activity when evaluating patients with AS and establishing a treatment plan.